Skarb z III okresu epoki brązu (Mont.) grupy konstantynowskiej kultury łużyckiej z Prawęcic w woj. łódzkim - Kaszowski, Zdzisław (Acta Universitatis Lodziensis. Folia Archaeologica, 1992)
A hoard of bronze ornaments came to light on 15 November 1981, while digging a potato pit on the farm of Waldemar Bednarek at Prawęcice, Aleksandrów commune, Łódź province. The find spot was located 5 m south of the newly constructed farm building and 50 m west of the Aleksandrów – Poddębice highway, at a depth of 70 cm below the ground surface, in a layer of yellow sand. The hoard, deposited in a pot, comprised 2 arm-rings with spiral plate ends of quadrate wire and 2 annular bracelets, sherds of further 5 vessels were found nearby. Arml-rings of this type are frequent in hoards of Bronze Age II and III recorded in Central Poland. However, they differ from the Prawęcice finds in the arrangement of ornament. On the basis of their decoration, the Prawęcice arm-rings have been assigned to the Miechowice type (Kuźnice variety). Massive annular bracelets occur rarely in Bronze Age finds from Central Poland, being mostly known from Lusatian hoards of the Konstantynów group. Potsherds found with the ornaments have numerous analogies in the Konstantynów group of the Lusatian culture. Owing to the presence of pottery with characteristics datable to the early phase of that culture, coeval with the first part of Bronze Age III, it is possible to assign the hoard to just that period. Its cultural identification also rests on pottery which is a diagnostic element. Accordingly, the Prawęcice hoard should by attributed to the Konstantynów group of the Lusatian culture.